Experimental Analysis of the Mechanisms of Reactive Mixing at the Seawater‐Freshwater Interface - Kevin DeVriendt; Tanguy LeBorgne; Joris Heyman; Maria Pool; Francesco Gomez; Yves Méheust; Marco Dentz (Water Resources Research)
Abstract The salt‐freshwater interface (SFI) in coastal aquifers, where water bodies of differing chemical compositions converge, represents as a hotspot for chemical disequilibrium and biogeochemical reactions. The interplay between variable density flow, mixing and reaction in porous media leads to complex and highly localized reaction patterns across the SFI, which are difficult to visualize, understand and model. In this study, we present a novel experimental setup to quantify mixing‐driven reactions at the SFI in a quasi two‐dimensional laboratory‐scale sand tank. We use a fast irreversible chemiluminescence reaction to obtain high resolution images of reaction intensity at the interface. We show that the reaction rate varies spatially along the interface, with up to a factor of four between minimum and maximum. We present a mechanistic model quantifying the evolution of the reaction rate along the interface by describing the coupled effects of solute dispersion, fluid compression and the change of the interface geometry under different flow rates. This modeling framework captures the spatial distribution of reaction along the SFI observed experimentally. It also explains and predicts the enhancement of the effective reaction rate across the interface when increasing freshwater flow. These findings provide a novel experimental technique and a new modeling framework to image and predict mixing‐driven chemical reactions in coastal aquifers.